Leadership as a Strategic Component in Building Competitive Advantage and Knowledge Creation - Morelato, Everton Vinicius; Cazane, Ana Lívia (Journal of Sustainable Competitive Intelligence, 2017)
Objective: This study aims to explore the role of leadership in building competitive advantage and generating new knowledge within organizations. Method: A descriptive, bibliographic research method was employed, focusing on relevant literature. The study reviewed theories on leadership, organizational culture, and their impact on knowledge generation. The research was structured into sections that discuss leadership concepts, organizational culture, and strategic leadership. Results: The study highlights that leadership, in conjunction with organizational culture, is crucial for fostering competitive advantage and promoting the creation of new knowledge. Effective leaders are able to create environments that encourage knowledge sharing and continuous learning, driving innovation and organizational growth. Conclusion: Leadership plays a strategic role in shaping organizational culture and facilitating knowledge creation. Leaders who can align cultural values with strategic objectives and foster knowledge-sharing behaviors are more likely to enhance their organization's competitive position.